Synthesis of Heptaprenyl-Lipid IV to Analyze Peptidoglycan Glycosyltransferases - Zhang, Yi (2007)
Bacteria are surrounded by a cell wall containing layers of peptidoglycan, the integrity of which is essential for bacterial survival. In the final stage of peptidoglycan biosynthesis, peptidoglycan glycosyltransferases (PGTs; also known as transglycosylases) catalyze the polymerization of Lipid II to form linear glycan chains. PGTs have tremendous potential as antibiotic targets, but the potential has not yet been realized. Mechanistic studies have been hampered by a lack of substrates to monitor enzymatic activity. We report here the total synthesis of heptaprenyl-Lipid IV and its use to study two different PGTs from E. coli. We show that one PGT can couple Lipid IV to itself whereas the other can only couple Lipid IV to Lipid II. These in vitro differences in enzymatic activity may reflect differences in the biological functions of the two major glycosyltransferases in E coli.